2010
DOI: 10.1089/ham.2009.1047
|View full text |Cite
|
Sign up to set email alerts
|

Altitude Illness in Qinghai–Tibet Railroad Passengers

Abstract: It takes ≈24 h to travel the ≈3000-km-long Qinghai–Tibet railroad of which 85% is situated above 4000 m with a pass at 5072 m. Each year about 2 million passengers are rapidly exposed to high altitude traveling on this train. The aim of this study was to quantify the occurrence of altitude illness on the train. Three subject groups were surveyed: 160 Han lowlanders, 62 Han immigrants living at 2200 to 2500 m, and 25 Tibetans living at 3700 to 4200 m. Passengers reached 4768 m from 2808 m in less than 1.5 h, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…However, it has been demonstrated that the prevalence of AMS is even greater and scarcely changes over the time, remaining at up to 50% in a mild form, after 12 years or more spent working in these shifts [11,15]. …”
Section: Chronic Intermittent Exposure To High-altitude Hypoxiamentioning
confidence: 99%
“…However, it has been demonstrated that the prevalence of AMS is even greater and scarcely changes over the time, remaining at up to 50% in a mild form, after 12 years or more spent working in these shifts [11,15]. …”
Section: Chronic Intermittent Exposure To High-altitude Hypoxiamentioning
confidence: 99%
“…The primary cause of AMS is atmospheric hypoxia, or a low oxygen level in the organs and tissues due to low partial pressure of oxygen (PAO 2 ) in air. [1][2][3] Hypoxia is involved the major biological pathways that contribute to human pathogeneses of the cardiovascular system, the respiratory system, neurophysiology, oncology, transplantation, and infectious diseases. 4 When the PAO 2 of air is less than 8 kPa (60 mmHg), the arterial oxygen content (CaO 2 ) and the arterial oxygen saturation (SaO 2 ) can significantly decrease and cause hypotonic hypoxemia (low arterial oxygen pressure, low saturation of hemoglobin by oxygen, and high hematocrit and hemoglobin concentrations).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of people live at a high altitude of more than 3000 meters around the world, especially in China (Wu et al, 2010). Moreover, there are also a number of people that ascend daily to these altitudes and are repeatedly exposed to hypoxia (Farias et al, 2006).…”
Section: Introductionmentioning
confidence: 99%